2018
DOI: 10.1186/s12860-018-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of the HIV-1 envelope transmembrane domain in intracellular sorting

Abstract: BackgroundThe envelope protein of lentiviruses are type I transmembrane proteins, and their transmembrane domain contains conserved potentially charged residues. This highly unusual feature would be expected to cause endoplasmic reticulum (ER) localization. The aim of this study was to determine by which means the HIV-1 Env protein is transported to the cell surface although its transmembrane domain contains a conserved arginine residue.ResultsWe expressed various chimeric proteins and analyzed the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Intracellular transport along the secretory pathway goes hand in hand with sorting of proteins and lipids (19). Hence, a possible role for 519 and 520 residues without expression and fusion activity is not recognized in the cellular transport and sorting machinery (20,21). These residues have an impact on localization of the protein in the compartment where their function is required.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular transport along the secretory pathway goes hand in hand with sorting of proteins and lipids (19). Hence, a possible role for 519 and 520 residues without expression and fusion activity is not recognized in the cellular transport and sorting machinery (20,21). These residues have an impact on localization of the protein in the compartment where their function is required.…”
Section: Discussionmentioning
confidence: 99%
“…This transport delay may be due to disrupted contacts of the individual trimer TMs with each other or through disruption of protein-membrane interactions. Further analysis of this region demonstrated that R696 does not confer a strict ER localization on the gp41 protein, despite the presence of charged residues within a TMD being a well-recognized ER localization motif [103]. Therefore, other elements in the HIV Env TMD, including its length, override the potential retention signal.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 98%
“…1E). Positively charged residues are vital for directing proteins into cell compartments or secretory pathways, [21][22][23] and altering the subcellular localization of a protein by site-directed insertions and/or deletions of positively charged residues in critical regions should be feasible. A multi-sequence alignment of all secretory human MMPs showed that the 88-123 region of MMP-26 is unique among all secretory MMPs (Fig.…”
Section: The 88-123 Region Of Mmp-26 Functions As An Er Retention Signalmentioning
confidence: 99%